2019
DOI: 10.1039/c8an01020j
|View full text |Cite
|
Sign up to set email alerts
|

DNA microarray analysis using a smartphone to detect the BRCA-1 gene

Abstract: DNA microarrays are used to examine changes in gene expression of a large number of genes simultaneously by fluorescent labeling of complementary DNAs (cDNAs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…This reagent consists of an aromatic amine sulphanilamide which reacts with nitrite to form a diazonium salt, which then combines with N-(1-naphthyl)-ethylenediamine dihydrochloride (NEDD) to form a pink colored azo dye [27]. Citric acid assessment was based on acid-base titration [21], such that the reaction of citric acid with sodium hydroxide reaches an equivalence point, else it climbs above this point (Figure 3b). For ascorbic acid, the LOD was found to be 1.47 µM with a linear range from 1–20 µM (Figure 3a), for glucose LOD was 20 mM with a linear range from 10–40 mM (Figure 3d), and for nitrite LOD was 0.06 mM with a linear range from 0.30–1.40 mM (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reagent consists of an aromatic amine sulphanilamide which reacts with nitrite to form a diazonium salt, which then combines with N-(1-naphthyl)-ethylenediamine dihydrochloride (NEDD) to form a pink colored azo dye [27]. Citric acid assessment was based on acid-base titration [21], such that the reaction of citric acid with sodium hydroxide reaches an equivalence point, else it climbs above this point (Figure 3b). For ascorbic acid, the LOD was found to be 1.47 µM with a linear range from 1–20 µM (Figure 3a), for glucose LOD was 20 mM with a linear range from 10–40 mM (Figure 3d), and for nitrite LOD was 0.06 mM with a linear range from 0.30–1.40 mM (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…For demonstration of paper based titration study, several channels were designed using AutoCAD 2016, printed (Xerox ColorQube 8580/N Wax Printer, Xerox Corporation, Norwalk, CT, USA), and baked (for 2 min @ 120 °C) [21] (Quincy Lab 20GC Gravity Lab, Chicago, IL, USA) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Summaries for the function of 4 significant genes. Biological information analysis has been widely applied to explore gene changes in the process of disease development, and this method may help scientists to identify new therapeutic targets [12][13][14] . A total of 371 DEGs, including 243 upregulated and 128 downregulated DEGs, were screened between NP cells cultured in hyperosmotic media and NP cells cultured in iso-osmotic media by analysing the biological data of the gene expression profile GSE1648.…”
Section: Sst Somatostatinmentioning
confidence: 99%
“…Regarding the pathological diagnosis, a recent study showed that easy, fast, and high-quality image capturing and transfer are possible from cytology slides using smartphones, with high intraobserver Kappa agreement (84.3%) between the microscopic cytopathological diagnoses and remote smartphone image diagnoses [30]. Smartphone-based molecular analyses are also being developed [60,61,62].…”
Section: Potential Impacts Of E-health In Oncologymentioning
confidence: 99%